Naive Bayes Classifier Method on Sentiment Analysis of Bibit Application Users in Play Store - Afifa Lufti Insani; Zamahsary Martha; Yenni Kurniawati; Zilrahmi (Departemen Statistika Universitas Negeri Padang, 2023)
The Bibit app is one of the most widely used investment apps these days. This application is widely used by novice investors because of its convenience in opening accounts, disbursing funds, purchasing mutual funds and easy-to-understand application design. However, there are still many people who doubt and worry about the quality of the Bibit application due to the lack of understanding of the advantages and disadvantages of the Bibit application. So, review data on the application is used which is available in the play store with the aim of knowing user reviews of the application and being a consideration for prospective users before using the application. Because reviews on the application have a large number and can be positive or negative, so sentiment analysis is needed that can help classify these reviews quickly. Then classification is carried out to obtain a classification model that can be used to predict user sentiment using the Naive Bayes Classifier method. The results obtained by Bibit application users tend to have positive sentiments with an accuracy value of 79.45%.